Does the intercept of the heat–stress relation provide an accurate estimate of cardiac activation heat?. (1st June 2017) - Pham, Toan; Tran, Kenneth; Mellor, Kimberley M; Hickey, Anthony; Power, Amelia; Ward, Marie‐Louise; Taberner, Andrew; Han, June‐Chiew; Loiselle, Denis
Abstract : Key points: The heat of activation of cardiac muscle reflects the metabolic cost of restoring ionic homeostasis following a contraction. The accuracy of its measurement depends critically on the abolition of crossbridge cycling. We abolished crossbridge activity in isolated rat ventricular trabeculae by use of blebbistatin, an agent that selectively inhibits myosin II ATPase. We found cardiac activation heat to be muscle length independent and to account for 15–20% of total heat production at body temperature. We conclude that it can be accurately estimated at minimal muscle length. Abstract: Activation heat arises from two sources during the contraction of striated muscle. It reflects the metabolic expenditure associated with Ca 2+ pumping by the sarcoplasmic reticular Ca 2+ ‐ATPase and Ca 2+ translocation by the Na + /Ca 2+ exchanger coupled to the Na +, K + ‐ATPase. In cardiac preparations, investigators are constrained in estimating its magnitude by reducing muscle length to the point where macroscopic twitch force vanishes. But this experimental protocol has been criticised since, at zero force, the observed heat may be contaminated by residual crossbridge cycling activity. To eliminate this concern, the putative thermal contribution from crossbridge cycling activity must be abolished, at least at minimal muscle length. We achieved this using blebbistatin, a selective inhibitor of myosin II ATPase. Using a microcalorimeter, we measured the force production and heat output, as functions of muscle length, of isolated rat trabeculae from both ventricles contracting isometrically at 5 Hz and at 37°C. In the presence of blebbistatin (15 μmol l −1 ), active force was zero but heat output remained constant, at all muscle lengths. Activation heat measured in the presence of blebbistatin was not different from that estimated from the intercept of the heat–stress relation in its absence. We thus reached two conclusions. First, activation heat is independent of muscle length. Second, residual crossbridge heat is negligible at zero active force; hence, the intercept of the cardiac heat–force relation provides an estimate of activation heat uncontaminated by crossbridge cycling. Both results resolve long‐standing disputes in the literature. Key points: The heat of activation of cardiac muscle reflects the metabolic cost of restoring ionic homeostasis following a contraction. The accuracy of its measurement depends critically on the abolition of crossbridge cycling. We abolished crossbridge activity in isolated rat ventricular trabeculae by use of blebbistatin, an agent that selectively inhibits myosin II ATPase. We found cardiac activation heat to be muscle length independent and to account for 15–20% of total heat production at body temperature. We conclude that it can be accurately estimated at minimal muscle length.